The Imagined and Real Jerusalem in Art and Architecture - Goudeau, Jeroen; Verhoeven, Mariëtte; Weijers, Wouter (Radboud Studies in Humanities, 2014)
In The Imagined and Real Jerusalem in Art and Architecture specialists in various fields of art history, from Early Christian times to the present, discuss in depth a series of Western artworks, artefacts, and buildings, which question the visualization of Jerusalem. Readership: All interested in art and architectural history, from the Early Christian times to the present, and anyone concerned with the history and the visual representation of Jerusalem.